Wide temperature lubrication of LST/PEO/Ag/MoS2 multilayer coating. (2nd January 2019) - Qin, Yongkun; Li, Yan; Xiong, Dangsheng; Li, Jianliang; Li, Zhuwen; Zhu, Xichang; Ge, Yan; Zhang, Rongchu
ABSTRACT: The Ag film and MoS2 film were successively deposited onto the LST/PEO duplex-treated titanium alloy substrate. The friction tests were conducted at 25°C, 350°C and 600°C, respectively. The worn morphologies were analysed by optical microscopy and Raman spectrum. The results showed that the LST/PEO/Ag/MoS2 coating exhibited more excellent friction behaviour in comparison to the LST/PEO coating at 25–600°C. The combined lubrication of Ag diffused from surface micro-pores and Ag2 MoO4 formed on the surface is responsible for the decrease of friction coefficient at 600°C. It also revealed that the friction heat can promote the formation of Ag2 MoO4 in comparison to the high test temperature.